Identifying a pathway towards recovery for depleted wild Pacific salmon populations in a large watershed under multiple stressors. Issue 9 (18th July 2022) - Chalifour, Lia; Holt, Cassandra; Camaclang, Abbey E.; Bradford, Michael J.; Dixon, Ross; Finn, Riley J. R.; Hemming, Victoria; Hinch, Scott G.; Levings, Colin D.; MacDuffee, Misty; Nishimura, Derek J. H.; Pearson, Michael; et al.
Abstract: Pacific salmon ( Oncorhynchus spp.) support coastal and freshwater ecosystems, economies and cultures, but many populations have declined. We used priority threat management (PTM), a decision‐support framework for prioritizing conservation investments, to identify management strategies that could support thriving populations of wild salmon over 25 years. We evaluated the potential benefits of 14 strategies spanning fisheries, habitat, pollution, pathogens, hatcheries and predation management dimensions on 19 conservation units (CUs)—genetically and ecologically distinct populations—of the five Pacific salmon species in the lower Fraser River, British Columbia, Canada. The PTM assessment indicated that under the current trajectory of 'business as usual', zero CUs were predicted to have >50% chance of thriving in 25 years. Implementation of all management strategies at an annual investment between 45 and 110 million CAD was, however, predicted to achieve >50% chance of thriving for most CUs ( n = 16), with nearly half (seven CUs) having a > 60% chance, indicating there is a pathway towards recovery for most populations if we invest now. In fact, substantial gains could be made by investing in five combined habitat strategies, costing 20M CAD annually. These habitat strategies were estimated to bring 14 of 19 salmon CUs above this 50% threshold. Co‐governance between First Nation and provincial and federal Canadian governments to manage salmon populations and harvest, and improved CU‐level monitoring emerged from the expert elicitation as critical 'enabling' strategies. By improving the feasibility of different management options, co‐governance brought an additional five CUs above the 60% threshold. Synthesis and applications. Supporting wild salmon in the face of cumulative threats will require strategic investment in effective management strategies, as identified by this priority threat management (PTM) assessment. PTM uses the best available data to objectively assess the potential outcomes of management alternatives. With renewed commitments from provincial and federal Canadian governments to protect and restore salmon populations and their habitats, positive conservation outcomes following implementation of targeted management strategies may be within reach. Abstract : Supporting wild salmon in the face of cumulative threats will require strategic investment in effective management strategies, as identified by this priority threat management (PTM) assessment. PTM uses the best available data to objectively assess the potential outcomes of management alternatives. With renewed commitments from provincial and federal Canadian governments to protect and restore salmon populations and their habitats, positive conservation outcomes following implementation of targeted management strategies may be within reach.